2004
DOI: 10.1016/j.critrevonc.2004.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Colon cancer

Abstract: Colon cancer is one of the leading tumours in the world and is considered among the big killers, together with lung, prostate and breast cancer. In the recent years very important advances occurred in the field of treatment of this frequent disease: adjuvant chemotherapy was demonstrated to be effective, chiefly in stage III patients, and surgery was optimized in order to achieve the best results with a low morbidity. Several new target-oriented drugs are under evaluation and some of them (cetuximab and bevaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 176 publications
(182 reference statements)
0
20
0
1
Order By: Relevance
“…Despite progress in early diagnosis and treatment of this cancer, aggressive surgical or chemotherapeutic interventions have not significantly improved the prognosis of patients with the advanced disease, particularly peritoneal carcinomatosis. 12 Recently, reports showed that the abnormal expression of RCK/p54 was closely related to malignant transformation and progression of colorectal cancer. 5 The RCK protein, RCK/p54, which is a 54-kDa cytoplasmic protein belonging to the DEAD …”
Section: Discussionmentioning
confidence: 99%
“…Despite progress in early diagnosis and treatment of this cancer, aggressive surgical or chemotherapeutic interventions have not significantly improved the prognosis of patients with the advanced disease, particularly peritoneal carcinomatosis. 12 Recently, reports showed that the abnormal expression of RCK/p54 was closely related to malignant transformation and progression of colorectal cancer. 5 The RCK protein, RCK/p54, which is a 54-kDa cytoplasmic protein belonging to the DEAD …”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of evidence that an individual's susceptibility to sCRC depends on both his/her an individual's genetic profile (so called "genetic makeup") and exposure to exogenous and endogenous carcinogens (DNA damaging agents) [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence is high, especially in developed countries, and it is now rising in developing countries like Thailand (Labianca et al, 2004;Khuhaprema and Srivatanakul, 2008). Genetics, environment, lifestyle, and diet are considered important factors that contribute to the development of colon cancer.…”
Section: Introductionmentioning
confidence: 99%